2014
DOI: 10.3109/13816810.2014.881507
|View full text |Cite
|
Sign up to set email alerts
|

Association ofLysyl oxidase (LOX)Polymorphisms with the Risk of Keratoconus in an Iranian Population

Abstract: Our study demonstrated that the LOX rs1800449 genotypes (AA and GA + AA) and allele (A) appears to confer risk for susceptibility to keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 36 publications
1
38
1
1
Order By: Relevance
“…8 The main statistics used here (allelic test) implicitly assume codominance, and is similar to the additive models assumed in the previous reports. 8,9,13,15 Although some caution is invited in the interpretation of our findings because of the relatively small sample size, the validation of rs2956540:G4C and rs3735520:G4A showing the same effect directions as previous studies in populations of European ancestry adds weight to the existing evidence. 8,9 Although not reaching a statistically significant threshold, the higher MAF of rs1800449:C4T and rs10519694:C4T in controls compared with the KC cases in our study, was consistent with protective effects of these alleles reported in another study using Caucasian case-control panels (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 47%
“…8 The main statistics used here (allelic test) implicitly assume codominance, and is similar to the additive models assumed in the previous reports. 8,9,13,15 Although some caution is invited in the interpretation of our findings because of the relatively small sample size, the validation of rs2956540:G4C and rs3735520:G4A showing the same effect directions as previous studies in populations of European ancestry adds weight to the existing evidence. 8,9 Although not reaching a statistically significant threshold, the higher MAF of rs1800449:C4T and rs10519694:C4T in controls compared with the KC cases in our study, was consistent with protective effects of these alleles reported in another study using Caucasian case-control panels (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 47%
“…1) 2124, 32, 37–54 . Among these 24 studies, 20 were candidate gene studies conducted in different populations, including Whites 39, 41, 43, 44, 47, 49–52, 55 , Arabic 37, 38, 40 , Chinese 45, 56 , Korean 53, 54 , Japanese 48 , Indian 46 , and Turkish 42 . The total sample sizes from these candidate gene studies were 3,037 patients with keratoconus and 9,928 controls.…”
Section: Resultsmentioning
confidence: 99%
“…136 Polymorphisms of the LOX coding gene are correlated with an increased likelihood to develop keratoconus. 137,138 In 63% of cases of keratoconus, LOX distribution has been found to be markedly decreased and its activity to be more than 2.5 times lower than that of control cases. 139,140 A study in Russia has shown that the increase in pH of the tears causes biochemical changes in the periphery of the cornea that prevent the passage of Keratoconus IL-1α, interleukin 1α; KC, keratoconous; β-NGF, nerve growth factor-β; PDGF, platelet-derived growth factor; PGE2, prostaglandin E2; PIGR, polymeric immunoglobulin receptor; RGP, rigid gas permeable; TGF-β1, transforming growth factor β1;…”
Section: Enzymatic Imbalancementioning
confidence: 99%